Development Of Vegetable-Oil-Based Polymers - Beg, M. D. H.; M. R., Islam; Saidatul Shima, Jamari (Wiley, 2014)
The utilization of renewable resources for the preparation of new materials is an alternative option for reducing the high demand of fossil feedstocks. Vegetable oils are potential bioresources that are renewable and abundantly available. Triglyceride-based vegetable oils, such as soybean, jatropha, linseed, sunflower, palm, castor, nahar seed, and canola oil, are being considered as precursors in the production of polymers. In this article, we attempt to summarize advancements in processes and technologies for the synthesis of polymers from various kinds of vegetable oils. The advantages and disadvantages of these biobased polymers with respect to traditional monomer-based ones are also highlighted.